Analisis Kualitas Depot Air Minum Isi Ulang Yang Ada Di Wilayah Puskesmas Tamalanrea - Toalu, Apdiani; Alwy, ST. Nurul Aliah; Baharuddin, Baharuddin; Nurhartati, Andi (JIMAD : Jurnal Ilmiah Multidisiplin, 2023)
Introduction: The Minister of Health Regulation (PERMENKES) No. 492 of 2010 states that drinking water is water that goes through a treatment process or without a treatment process that meets health requirements and can be drunk directly. Population growth, which increases rapidly every year, is one of the factors causing groundwater pollution that is getting worse until now, so that the availability of proper drinking water is decreasing. This is what encourages the emergence of business entities that treat raw water into water that is ready to drink. Objective: to determine whether or not the quality of drinking water produced by the Refill Drinking Water Depot in the Tamalanrea Health Center working area is feasible. Methods: The type of research conducted is experimental research which is a physical, chemical and microbiological laboratory study of drinking water produced by the Refillable Drinking Water Depot in the Tamalanrea Health Center area and at the Makassar City Health Office Laboratory based on 32 samples on July 21, 2020. Results: physical parameters can be done by looking and observing directly whether the water is colored, smells, tastes or not. For chemical tests the sample is carried out by the UV-Vis method, microbiological parameters (Escherichia Coli) or the number of Escherichia Coli in the sample. Conclusion: 1. The results obtained from 27 depots (32 samples) studied showed that all depots in the Tamalanrea Health Center area met the requirements (100%) in terms of physical parameters, chemical parameters, where the results obtained that all drinking water from the depot was odorless. 2. The results obtained show that of the 27 depots (32 samples) examined, 18 depots studied in the Tamalanrea Health Center area are Qualified (59.26%) and 9 depots are Not Qualified (40.74%).